BASED ON ENERGY EFFICIENT PARAMETERS OF FRUIT DRYING CHAMBER DEVICES FOR SMALL ENTERPRISES - Rozikova, Dilshoda; Kurbanov, Ne'matilla (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Identifying the biological characteristics of the date fruit set as tasks in the organization of the technology of artificial drying of date fruit and skin; Analysis of widely used varieties in Uzbekistan; determining the main technological processes; biological properties and determination of the composition of the finished powder and the secondary filler. Expanding the assortment of agricultural products and providing the population with environmentally friendly food products is becoming one of the urgent issues. Development of an energy-efficient improved device that dries agricultural products in sufficient quantity with low consumption costs, as well as justification of its main parameters, efficient use of energy is directed to the main tasks. The drying chamber consists of two modules (drums) moving against the flow of hot air, and in the process of drying raw materials, it makes efficient use of time and leads to the drying of quality products in an energy-efficient way.